A Comparative Analysis of Ulama Opinions on the Existence of the Sighat Ta'liq Talaq in Indonesia - Ahmad Fizal (Al Mashaadir : Jurnal Ilmu Syariah, 2025)
This research is descriptive-analytical in nature, aiming to describe the object of study while also conducting an in-depth analysis of it. The research method used is qualitative research, specifically library research, employing a qualitative descriptive approach that focuses on theories, concepts, and ideas. This approach seeks to reveal or describe the data or theories obtained. In classical Islamic jurisprudence (fiqh), particularly within the Shafi'i school of thought, ta'liq talaq (conditional divorce) is considered a unilateral declaration by the husband that links the occurrence of divorce to a specific condition. If the husband violates the agreement, the divorce is deemed to take effect automatically—without the wife's consent or a ruling from the religious court. However, in practice, this can lead to legal uncertainty and the potential for abuse. In contrast, under the Compilation of Islamic Law (KHI) as applied in Indonesia, ta'liq talaq is more formally and procedurally regulated. Article 45 of the KHI states that ta'liq talaq may be established as a valid marital agreement, but its declaration is not mandatory. If it is declared, it must be recorded in the marriage certificate and signed by the husband as authentic evidence. A violation of this conditional divorce agreement can only be used as a ground for divorce if submitted through a formal divorce application to the Religious Court, and the resulting divorce is not automatically considered a triple divorce (talaq tiga). According to a dictionary of fiqh terms, ta'liq talaq is defined as "making the occurrence of divorce dependent on a particular condition—thus, the divorce becomes effective when the condition is met." Meanwhile, the Compilation of Islamic Law defines ta'liq talaq as a marital agreement declared by the groom after the marriage contract, included in the marriage certificate, which contains a promise of divorce contingent on the occurrence of a certain condition in the future. The form of ta'liq talaq in Indonesia—its structure and the conditions for its establishment—differs from the concept of ta'liq talaq found in classical fiqh literature. Its content is no longer a threat from the husband to the wife, but rather a promise by the husband to treat his wife well and live with her in accordance with mu‘āsharah bi al-ma‘rūf (kind and proper companionship) as prescribed by Islamic law. Therefore, in this study, the author will describe various scholarly opinions regarding the legal status and interpretation of ta'liq talaq within the framework of Islamic jurisprudence.